A prospective study of single layer abdominal wall closure in the tertiary care hospital - Agrawal, Sujan Narayan; Singh, Kameshwar (International Surgery Journal, 2019)
Background: Despite advances in surgical techniques and material, abdominal wound closure remains challenging. Most abdominal wall incisions are either midline or paramedian. The value of a particular method of closing is determined by the incidence of early and late wound complications. The best abdominal wound closure technique should be, fast, easy, safe and cost effective. It should also prevent or minimize the early and late complications. This study addresses the midline single-layer closure of the abdominal wound. Methods: The purpose of this study is to evaluate the single layer midline abdominal wound closure. The early and late complications associated with this method are studied, and relevant literature reviewed. The study period is from May 2016 to May 2018, i.e. 24 months. The study group comprises of 52 patients, admitted in the department of surgery SBRKM Government medical college Jagdalpur. In all of them, the midline incisions closed in a single layer by a non-absorbable continuous suture. The skin closed separately. The mean age of the patient is 46.5 years. The male to female ratio is 3:1. Emergency laparotomy done in 35 cases and 17 (38.4%) underwent elective surgeries. Results: In this series 20 (38.4%) patients had wound infection. 10 (19.2%) patients had wound gaping. There was no incisional hernia in six months follow-up. Conclusions: Single layer abdominal wall closure has a definite advantage. It is fast, easy and cost-effective. Continuous running suture with non-absorbable material provides enough strength during healing and is better than interrupted sutures. The incidence of early and late complications is also significantly less. The results are comparable to many meta-analyses and RCT did in this field.